Synthesis of beta-amino alcohols from aromatic amines and alkylene carbonates using Na-Y zeolite catalyst - Shivarkar, Anandkumar B.; Gupte, Sunil P.; Chaudhari, Raghunath V. (Synlett, 2006)
A simple, efficient, and environmentally benign methodology for the synthesis of beta-amino alcohols from aromatic amines and alkylene carbonates in the presence of the highly active and reusable solid base catalyst Na-Y zeolite is demonstrated.
Keywords: Alkylation; alkylene carbonate; Amine; Amino alcohols; zeolite